Enzymatic hydrolysis of cassava stalks pretreated with the alkaline method (2015)
ABSTRACT: This study was developed with the aim of evaluating the pH, enzymatic complex load and temperature effects on the saccharification of pretreated cassava stalks (CS) using the response surface methodology (RSM). The factor levels evaluated were temperature 35-40°C, pH 4.0-5.0 and dose of enzymatic complex Accellerase 1500™ 2.9 - 14.5 FPU/g of substrate. The reducing sugar (RS) response was used. The pH was controlled through the use of hydrochloric acid and sodium hydroxide solutions and the system was shaken orbitally at 120 rpm with a solids loading of 10% w/v. The fitted model showed that the optimal operating conditions were: pH 4.0, 38°C and enzyme dose of 14.5 FPU/g substrate, reaching a sugar concentration of 18.4 g L-1.